Transversus abdominis plane block supplementation during iliac crest bone graft harvesting - Effect on postoperative pain - Usha Shenoy; Vigil Peter; Philip Mathew; Tom Thomas (Wolters Kluwer Medknow Publications, 2018)
Background and Aims: Transversus abdominis plane (TAP) block is a technique proposed to minimise pain after anterior iliac crest bone harvesting. This study aims to evaluate the postoperative pain in patients who receive ultrasound-guided TAP block to supplement routine wound infiltration. Material and Methods: A total of 143 patients aged between 6 and 22 years were randomised into two groups. Patients in group A received supplemental TAP block on the same side. Patients in group B received local anesthetic wound infiltration alone. Pain scores were compared at the first and 24th postoperative hours. Results: TAP block significantly reduced pain and delirium in the immediate postoperative period. The mean FLACC (Face, Legs, Activity, Cry, Consolability) score after 10 min was 0.8 in group A versus 1.8 in group B (P = 0.001). The mean Watcha scale at 10 min was 1.0 in group A versus 1.2 in group B (P = 0.001). After 24 h, 81.7% of patients in group A had no pain versus 59.7% in group B (P = 0.004). The incidence of intolerable pain at 24 h was 5.6% in group B versus 0% in group A (P = 0.04). Cumulative ambulation scores were significantly better in group A (P < 0.05). There was a strong and positive correlation between the analgesia and ability to ambulate comfortably at 24 h postop (Pearson's coefficient 0.95). Conclusion: Supplemental ultrasound-guided TAP block given intraoperatively reduces the postoperative pain. The incidence of emergence delirium was low. These patients were also able to ambulate earlier.